Kokoda - Ham, Paul (HarperCollins, 2004)
Focussing on the infamous Kokoda Track campaign, this tale has been told from both sides of the conflict. In a balanced portrayal, it also recounts both the Australian and Japanese perspectives of the hellish Papuan jungle trail.